A Note on the ⊤-Stein Matrix Equation. (7th August 2013) - Chiang, Chun-Yueh
Abstract : This note is concerned with the linear matrix equation X = A X ⊤ B  +  C, where the operator ( · ) ⊤ denotes the transpose (⊤ ) of a matrix. The first part of this paper sets forth the necessary and sufficient conditions for the unique solvability of the solution X . The second part of this paper aims to provide a comprehensive treatment of the relationship between the theory of the generalized eigenvalue problem and the theory of the linear matrix equation. The final part of this paper starts with a brief review of numerical methods for solving the linear matrix equation. In relation to the computed methods, knowledge of the residual is discussed. An expression related to the backward error of an approximate solution is obtained; it shows that a small backward error implies a small residual. Just like the discussion of linear matrix equations, perturbation bounds for solving the linear matrix equation are also proposed in this work.